La Loaded TiO2 Encapsulated Zeolite Y Catalysts: Investigating the Characterization and Decolorization Process of Amaranth Dye - Atheel Hassan Alwash; Ahmad Zuhairi Abdullah; Norli Ismail (Journal of Engineering)
Lanthanide ions loaded TiO2 encapsulated into Y zeolite catalysts were synthesized and used in sonocatalytic degradation of Amaranth dye in aqueous solution. The support zeolite Y was modified by different loading of Ti and La species using ion exchange method. The sonocatalytic reaction condition was carried out at 10 mg/L initial dye concentration, original pH, 1.5 g/L of catalyst loading with low ultrasonic frequency of 40 KHz. Different characterization techniques were used to reveal the physicochemical characteristics of the catalysts. Successful loading of TiO2 and La/TiO2 into zeolite Y was achieved. The framework of zeolite Y remained unchanged after the loading of TiO2. Titanium species was bound to the framework of zeolite through Ti–O–Si bonds through isomorphous substitution of Si in the zeolite. The ultrasonic degradation of Amaranth dye was enhanced by the TiO2 encapsulation with a maximum degradation efficiency of 50% after 120 min of reaction. However, the activity of the catalyst decreased after the loading of lanthanum. This decrease was attributed to the poor contact between the metal crystallites located on the external surface and the titanium encapsulated into cages of zeolite Y.